The Determinants of Effectiveness Online Learning Media: A Case Study In Accounting Study Program at Universitas Medan Area - Aditya Amanda Pane; T. Alvi Syahri Mahzura; Rana Fathinah Ananda; Sari Nuzullina Rahmadhani; Atika Rizki (Universitas Padjadjaran, 2022)
This study aims to analyze the effectiveness of online learning in terms of student perceptions, emotional intelligence, and the use of online media during the covid-19 pandemic. This quantitative research approach uses a questionnaire survey technique and descriptive data analysis. The sampling technique is simple random sampling, and the sample obtained research is an active student of Accounting Studies Program at the Universitas Medan Area semesters 2, 4, and 6. The research results show that the perception of students on learning online in the past pandemics Covid-19 through a various selection of media online considered effective and help improve students' emotional intelligence